'[N]ow I can be a poetic writer': using action research as a way of reclaiming and implementing professional values in the primary school. Issue 1 (1st January 2022) - Weber, Stephanie; Harris, Rebecca
ABSTRACT: This paper explores the impact of an action research intervention to support primary aged children's confidence as writers. Set in a school where few children (the majority of whom had English as an additional language) were performing at or beyond national expectations in terms of writing, the intervention looked at how to engage children more effectively, by promoting enjoyment of writing and providing quality mentor texts to inspire the children. The school had received a number of critical inspection reports and had consequently adopted a series of measures to improve academic outcomes, which acted as a constraint on my teaching. There was a real sense that as a teacher I was struggling to put my educational values into practice. In addition, my lack of confidence in my abilities as a writer acted as a further constraint. Adopting an action research approach enabled me to develop my personal confidence as a teacher of writing, explore more effective ways to teach writing, resulting in the development of confident and reflective writers in the classroom.